2019
DOI: 10.1038/s41557-019-0249-2
|View full text |Cite
|
Sign up to set email alerts
|

Closed-loop recycling of plastics enabled by dynamic covalent diketoenamine bonds

Abstract: Recycled plastics are low-value commodities due to residual impurities and the degradation of polymer properties with each cycle of re-use. Plastics that undergo reversible polymerization allow high-value monomers to be recovered and re-manufactured into pristine materials, which should incentivize recycling in closedloop life cycles. However, monomer recovery is often costly, incompatible with complex mixtures, and energy-intensive. Here, we show that next-generation plastics-polymerized using dynamic covalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
469
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 530 publications
(501 citation statements)
references
References 43 publications
6
469
0
2
Order By: Relevance
“…More importantly,o ur approach is an ovel and alternative strategy for recycling thermosetting materials. [58][59][60] This proposed photoresponsive mechanism was further confirmed based on the results from control experiments. After exposure to UV light for 10 min, the tensile strength values decreased by ca.…”
Section: Angewandte Chemiementioning
confidence: 54%
See 1 more Smart Citation
“…More importantly,o ur approach is an ovel and alternative strategy for recycling thermosetting materials. [58][59][60] This proposed photoresponsive mechanism was further confirmed based on the results from control experiments. After exposure to UV light for 10 min, the tensile strength values decreased by ca.…”
Section: Angewandte Chemiementioning
confidence: 54%
“…These results provide evidence for the proposed photoreduction and thermal oxidation mechanism. More importantly, our approach is a novel and alternative strategy for recycling thermosetting materials …”
Section: Resultsmentioning
confidence: 99%
“…The cross‐linking density of a vitrimer influences its thermal and mechanical properties: for example, higher network density increases the probability that cross‐links will interact and be involved in bond‐exchange reactions, which impact the dynamics of vitrimer reconfigurability across multiple length scales and therefore its rheology. The energetics of bond‐exchange reactions have been studied for vitrimers undergoing uncatalyzed or catalyzed transesterification, transcarbamoylation, olefin metathesis, boronic ester exchange, siloxane exchange, triazolium transalkylation, imine bond exchange, ketoenamine exchange, and diketoenamine exchange . However, there is a lack of understanding of how conformational degrees of freedom available to the network influence a vitrimer's thermal and rheological behavior in and out of equilibrium.…”
Section: Figurementioning
confidence: 99%
“…Herein, we show that the incorporation of conformationally flexible or, alternatively, stiff ditopic (A2) monomers into a vitrimer network otherwise comprised of tritopic (A3) and ditopic B2 monomers allows the network density to be independently modulated from the thermal, mechanical, and rheological properties of the network. We exerted fine‐control over such architectural attributes in a vitrimer using poly(diketoenamine)s, or PDKs, which click together via spontaneous condensation reactions between polytopic triketone and amine monomers (Figure a) . PDK 1 , which exhibits the highest network density, was generated from ditopic triketone monomer TK‐10 and tris(aminoethyl)amine (TREN) as the crosslinker.…”
Section: Figurementioning
confidence: 99%
“…Amazingly, it is reported that only 10 % of plastics are recycled in the United States, the superpower with advanced technology . On the one hand, we may absolutely turn our attention to inventing degradable plastics . But the cost and condition of degradation are main challenges.…”
Section: Introductionmentioning
confidence: 99%